ANALISIS KEMAMPUAN BERBICARA SISWA KELAS IV SD DALAM PEMBELAJARAN MENDONGENG - FauziaSilviani, Bestari; Sulaiman, Zoni; Nuriyanti, Risma (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the speaking ability of fourth-grade elementary school students in storytelling learning activities, focusing on speaking fluency, pronunciation and intonation, and story mastery. Speaking ability is an essential language skill that supports students’ communication competence; however, many elementary school students still encounter difficulties in expressing ideas fluently, delivering stories coherently, and speaking confidently in front of an audience. Storytelling is considered an effective learning activity because it provides students with opportunities to practice oral communication in a meaningful and engaging context. This study employs a descriptive qualitative approach. The participants are fourth-grade elementary school students. Data were collected through a storytelling performance test designed to assess students’ speaking abilities based on indicators of fluency, pronunciation and intonation, and story mastery. The data were analyzed through data reduction, data presentation, and conclusion drawing. The findings are expected to provide a comprehensive description of students’ speaking abilities in storytelling activities and to identify their strengths and weaknesses in each assessed aspect. Furthermore, the results are expected to contribute to the development of effective learning strategies for improving speaking skills and serve as a reference for teachers in designing more interactive and communicative language learning activities in elementary schools.